Corporate Transparency and Environmental Reporting: Trends and Benefits - Farooq, Umar (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
Purpose: This study investigates the role of corporate transparency in environmental reporting, emphasizing its impact on accountability, stakeholder trust, and sustainable business practices. It examines current trends, benefits, and challenges associated with environmental reporting frameworks while exploring how digital technologies enhance reporting accuracy and credibility. Research Design and Methodology: This study analyzes peer-reviewed articles, industry reports, and regulatory frameworks published after 2018. The focus includes globally recognized standards such as the Global Reporting Initiative (GRI), Sustainability Accounting Standards Board (SASB), and Task Force on Climate-related Financial Disclosures (TCFD), along with technological advancements like blockchain, big data analytics, and artificial intelligence (AI). Findings and Discussion: The study finds that transparent environmental reporting enhances corporate accountability, strengthens stakeholder relationships, and facilitates access to sustainable investments. Companies adopting robust frameworks effectively manage environmental risks and build stakeholder trust. However, challenges persist, including inconsistent standards, greenwashing risks, and the need for third-party verification. Digital technologies are key solutions for enhancing reporting accuracy, verifiability, and comprehensiveness. Implications: This study provides practical recommendations for companies, policymakers, and stakeholders, advocating for standardized frameworks and technological integration. It highlights the need for future research to address sector-specific challenges and assess the long-term impact of transparent environmental reporting on corporate sustainability.